PTH-096 The Sensitivity Of Eus Fna Of Solid Pancreatic Lesions, Working From A Regional Mdt And Within A Regional Network. (9th June 2014) - Gordon, H; Lloyd, D; Higginson, A; McCrudden, R; Bent, C; Shek, F; Beable, R; Al-Badri, A; Green, B; Jaynes, E; Collins, D; Poller, D; et al.
Abstract : Introduction: Endoscopic ultrasound (EUS) guided sampling of advanced malignant pancreatic lesions is increasingly being performed in order to confirm malignancy prior to chemotherapy and or treatment. Meta-analysis of 33 studies examining solid lesion EUS FNA tissue acquisition in 4984 patients showed a pooled sensitivity of 85%, increasing to 91% if suspicious atypia was included 1 . Higher sensitivities have been demonstrated in large volume single operator centres where sensitivities of 92–97% 2, 3 have been reported. The four Wessex EUS centres all work from a regional HPB MDT, where pancreatic cases are discussed and EUS procedures requested. Each centre has two EUS operators, performing between 148 and 214 cases per annum. Additionally the regional EUS endoscopists, pathologists and biomedical technicians meet three times a year for EUS network meetings to audit outcomes and review practice standards. In 3 of the 4 centres cytopathology staff are present in the endoscopy room to provide rapid on site evaluation and confirm adequate sample cellularity and give a preliminary diagnosis. Methods: Each centre prospectively audited the results of EUS guided biopsy of suspected malignant solid pancreatic lesions over a 6 month period from 1.7.13 to 31.12.13. From this data the true positive rate was calculated to determine if such networking produced results comparable to large volume single centres. Results: There was a regional sensitivity of 96%. The majority of lesions were adenocarcinoma but other results included: 1 lymphoma, 8 neuroendocrine tumours, 1 renal cell cancer metastasis. Conclusion: A regional sensitivity of 96% is comparable with results from a single large volume UK EUS centre. This demonstrates that smaller volume centres working within a regional network can achieve similar standards to high volume centres. References: 1 Hewitt et al. GI Endoscopy 2012; 75 (2):319–331 2 Cherian et al. HPB 2010; 12 (6):389–395 3 Manzia et al. Annals of RC Surgeons England 2010; 92 (4):295–301 Disclosure of Interest: None Declared.